Colonic Atresia: A Case Report - Nessa, Meherun; Khan, Shams ud Din Elias; Hossain, Md Shakhawat (Journal of Armed Forces Medical College, Bangladesh, 2016)
Atresia of the colon is among the rare types of all gastrointestinal atresias. Descending colon is the rarest site of all the colonic atresias. A case report of 3 days old female baby was presented with the features of distal intestinal obstruction. At laparotomy type I atresia of the middle part of asending colon, with proximal dilatation of caecum and ilum. Microcolon was noticed in ascending colon, transverse colon, descending colon and sigmoid colon when newborn underwent exploration. Primary ileostomy and distal mucus stoma of ascending colon was done. After four weeks, closure of ostomy was done. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 116-119